Traditional Chinese Medicine (TCM) in the treatment of COVID-19 and other viral infections: Efficacies and mechanisms - Huang, Kai; Zhang, Pan; Zhang, Zhenghao; Youn, Ji Youn; Wang, Chen; Zhang, Hongchun; Cai, Hua (Pharmacology & therapeutics (Oxford), 2021)
COVID-19 has remained an uncontained, worldwide pandemic. While battling for the disease in China, six Traditional Chinese Medicine (TCM) recipes have been shown to be remarkably effective for treating patients with COVID-19. The present review discusses principles of TCM in curing infectious disease, and clinical evidence and mechanisms of the 6 most effective TCM recipes used in treating COVID-19 in 92% of all of the confirmed cases in China. Applications of TCM and specific recipes in the treatment of other viral infections, such as those caused by SARS-CoV, MERS-CoV, hepatitis B virus, hepatitis C virus, influenza A virus (including H1N1 and H7N9), influenza B, dengue virus as well as Ebola virus, are also discussed. Among the 6 TCM recipes, Jinhua Qinggan (JHQG) granules and Lianhua Qingwen (LHQW) capsules are recommended during medical observation; Lung Cleansing and Detoxifying Decoction (LCDD) is recommended for the treatment of both severe and non-severe patients; Xuanfeibaidu (XFBD) granules are recommended for treating moderate cases; while Huashibaidu (HSBD) and Xuebijing (XBJ) have been used in managing severe cases effectively. The common components and the active ingredients of the six TCM recipes have been summarized to reveal most promising drug candidates. The potential molecular mechanisms of the active ingredients in the six TCM recipes that target ACE2, 3CLpro and IL-6, revealed by molecular biological studies and/or network pharmacology prediction/molecular docking analysis/visualization analysis, are fully discussed. Therefore, further investigation of these TCM recipes may be of high translational value in enabling novel targeted therapies for COVID-19, potentially via purification and characterization of the active ingredients in the effective TCM recipes.